Remote viewing: a brief historical inquiry into theatre and social distance. Issue 3 (1st September 2020) - Starner, Andrew
ABSTRACT: This article takes up the complicated relationship between audience presence and absence by exploring a series of historical theatre examples alongside contemporary performances. These juxtapositions aim to engender a better understanding of the ways that theatrical audiences are conceived and addressed on screens, a phenomenon best characterized as televisual theatre. Live performance has always created the conditions for bracketing and enlarging moments of time and suturing spaces of unusual significance. We zoomed in theatre long before we zoomed optically through telescopic lenses or, more recently, thanks to videoconferencing. But if we stop to think about it, our experiences are just as often about being out of synch – before or after an imagined experience (of spectating, even). And while a viewer can't have the same level of 'access' to a performance when watching it on a video screen (notably, he/she can't interrupt the performance, whether intentionally or not), the viewer becomes a 'second' audience that nevertheless retains key attributes of the 'first' audience. Now, more than ever, the desire for contact and connection is emerging as a key concern for theatre practitioners and theorists. The long history of remote viewing in the theatre may offer some cause for optimism.